Comparing the survivability of various probiotic strains through the pelleting process - Jacobs, R.; Ayala, D.; Dunmire, K.; Gordon, M.E. (Journal of equine veterinary science, 2025)
The widely accepted definition for probiotics specifies that they are “live microorganisms which when administered in adequate amounts confer a health benefit on the host.” The specific reference to “live microorganisms” is of paramount importance when discussing the efficacy of these bacteria. Commonly, equine feeds and supplements that contain claimed probiotics are provided to the horse in a pelleted form, which are produced utilizing high temperatures, pressures, and moisture via steam addition, which are all factors known to inactivate certain bacteria. The objective of this study was to evaluate the post-pelleting survivability of a selection of bacteria with proposed probiotic properties. Four bacteria commonly used in equine probiotic supplements were obtained (Enterococcus faecium, Lactobacillus reuteri, Lactobacillus casei, and Bifidobacterium longum; Waseen Inc.). A fifth bacterium of interest was also evaluated (Bacillus coagulans GBI-30, 6086; Kerry). Identical alfalfa-based premixes were prepared with a targeted concentration of 1.13 × 109 cfu/kg of each bacterium. Premixes were mixed utilizing a ribbon mixer and pelleted using a 100-hp dual-speed pellet mill (CPM, model 2S) using a 5/32-inch pellet die at a rate of 54.5 kg/min and a conditioning temperature of 85 C. Two samples (25 g) of each pre- and post-pelleting feed sample was added to 225 mL of buffered peptone water (BPW). To evaluate the viability of B. coagulans GBI-30, 6086, E. faecium, B. longum, L. casei, and L. reuteri, samples were homogenized in a stomacher at 230 rpm for 2 min, diluted on BPW, and plated in selective media. Plates were then incubated at respective conditions for 24 to 48 h: Luria–Bertani 42°C; brain heart infusion 42°C; de Man, Rogosa, and Sharpe (MRS) 37°C anaerobically; and MRS 37°C aerobically. Plates with 25 to 250 colonies were counted and results recorded as log10 cfu per gram. Data were analyzed via ANOVA using a MIXED procedure (SAS 9.4). Pre- and post-pelleting data are presented in Table 1. Taken together, these data demonstrate that a selection of bacteria commonly used in equine feeds and supplements do not meet the definition of probiotic when provided in a pelleted form. In addition, this type of research can act as a screening tool to determine which probiotics should be the subject of additional physiological research in horses. Bacillus coagulans GBI-30, 6086 is a unique sporeforming bacterium which survives pelleting, enabling it to function as a probiotic in the horse.